2009
DOI: 10.1210/jc.2008-1252
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of Luteinizing Hormone (Gonadotropin-Releasing Hormone) Secretion across Puberty: Evidence for Altered Regulation in Obese Peripubertal Girls

Abstract: Obesity in prepubertal and early pubertal girls is associated with reduced LH secretion and reduced nocturnal changes of LH. In later pubertal girls, obesity is linked with reduced LH amplitude, but elevated LH frequency; the latter may reflect effects of hyperandrogenemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
99
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(108 citation statements)
references
References 39 publications
6
99
0
3
Order By: Relevance
“…Our findings are further supported by studies showing lower gonadotropin and E 2 levels in early-to-mid-pubertal obese girls compared with similarly matured normal-weight girls (22). In accordance, we found that pubertal girls with adiposity O29% had lower gonadotropin levels compared with the normal-weight pubertal girls.…”
Section: Clinical Studysupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings are further supported by studies showing lower gonadotropin and E 2 levels in early-to-mid-pubertal obese girls compared with similarly matured normal-weight girls (22). In accordance, we found that pubertal girls with adiposity O29% had lower gonadotropin levels compared with the normal-weight pubertal girls.…”
Section: Clinical Studysupporting
confidence: 90%
“…In addition, higher BMI and skin fold thickness in infancy and childhood seem to predict earlier onset of breast development and menarche (18,19,20,21). However, reproductive hormone levels have been reported to be lower in obese compared with normal-weight pubertal girls (22). Thus, inconsistency exists between the findings reported from the population-based studies relying solely on pubertal staging and studies reporting possible effects of obesity on the activation of the hypothalamic-pituitary-gonadal axis.…”
Section: Introductionmentioning
confidence: 99%
“…Obese woman had significantly lower LH level responses to GnRH than the normal-weight group (17). Similar data also exist in obese girls without precocious puberty (2,6,7,18). Overweight early pubertal girls had significant blunting of sleeprelated LH production, which is the first hormonal change of puberty.…”
Section: Discussionsupporting
confidence: 63%
“…Obesity in prepubertal and early pubertal girls was associated with reduced overnight LH secretion, while obesity was linked to reduced LH pulse amplitude, but elevated LH pulse frequency, in late pubertal girls (20). In adolescent obese girls with menarche, a reduced ratio between LH and the FSH was observed after weight loss (21).…”
Section: Introductionmentioning
confidence: 98%